Business location recommendation using check-in data - Ahmed, Nasim Uddin; Mahmud, Shafayet; Islam, Md. Tawabul; Shoumik, Shadman; Habib, Muhaimin (BRAC University, 2018)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.